FDI Spillovers in Emerging Markets: Does Economic Policy Uncertainty and Geopolitical Risk Matter? - Kunjal, Damien; Mutemeri, Linah; Naidoo, Yuthika; Moodley, Saien; Reddy, Tharosha; Govender, Keshav; Msomi, Wendile (Organizations and Markets in Emerging Economies, 2025)
This study investigates the influence of economic policy uncertainty (EPU) and geopolitical risk (GPR) on the spillovers of foreign direct investment (FDI) within emerging markets, represented by the BRICS (Brazil, Russia, India, China, and South Africa) nations. Using a Time-Varying Parameter Vector Autoregressive (TVP-VAR) model and a dynamic Diebold and Yilmaz (DY) (2012) spillover index, the research assesses the interconnectedness and spillover effects of FDI flows among the BRICS countries over a 25-year period (1998–2023). The findings reveal significant spillover effects in the FDI of the BRICS nations, with Russia being a net transmitter and China a net receiver. Moreover, EPU and GPR significantly influence these FDI spillovers, with the effect of GPR being more predominant, highlighting the increased sensitivity of emerging markets to economic and geopolitical risks. Therefore, these findings underscore the role of coordinated policy measures in mitigating systemic risks and enhancing resilience against geopolitical and economic shocks. Overall, this study represents a novel contribution to existing literature by providing insight into the impacts of economic policy and geopolitical uncertainties on spillovers of foreign financial flows in emerging markets, particularly the BRICS nations.
Keywords: Economic policy uncertainty; Foreign Direct Investment; Geopolitical risk; Interconnectedness